Effect Of Lanthanum Oxide (La2O3) Addition On The Properties Of Calcium Copper Titanate (CaCu3Ti4O12) - Sharif, Nur Shafiza Afzan (2010)
The electroceramic of CaCu3Ti4O12 (CCTO) was prepared by solid state reaction method using three main raw materials of Ca(OH)2, CuO, and TiO2 powders. This study was focused in characterization of CCTO properties which was calcined and sintered through conventional and microwave sintering techniques. La doping method was applied to CCTO with substitution of Ca from 1 to 10 mole %. The starting materials were wet mixed, calcined, formed by pressing, and finally were sintered according the processing flow. The mixed powder was calcined at temperature of 900 ºC for 12 hours using furnace to form the CCTO compound.